2019
DOI: 10.4018/978-1-5225-7885-7.ch006
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone Usage, Gratifications, and Addiction

Abstract: Combining a survey and focus groups as a mixed-methods research, the authors of this chapter examined the functions, types, and motivations of smartphone usage and gratifications. Furthermore, the authors also investigated the rates, symptoms, and reasons of smartphone addiction. Still another achievement of the authors was to look into the relationship between smartphone usage, gratifications, and addiction with academic achievements among college students. On top of identifying three levels of addiction, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 32 publications
2
9
0
Order By: Relevance
“…At a very basic level, smartphones are popular because they enable individuals to keep their minds occupied and to feel connected. These findings are consistent with previous studies that have found a number of positive motivations for people to use smartphones (Livingston, 2010;Tillander, 2011;Agarwal, 2014;Pew Research, 2017;AlBarashdi and Bouazza, 2019). As Annoni et al (2021) found a continuous search for connections is one of the primary drivers for smartphone use.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…At a very basic level, smartphones are popular because they enable individuals to keep their minds occupied and to feel connected. These findings are consistent with previous studies that have found a number of positive motivations for people to use smartphones (Livingston, 2010;Tillander, 2011;Agarwal, 2014;Pew Research, 2017;AlBarashdi and Bouazza, 2019). As Annoni et al (2021) found a continuous search for connections is one of the primary drivers for smartphone use.…”
Section: Discussionsupporting
confidence: 91%
“…These benefits are also seen in some prior studies e.g. Agarwal (2014), Pew Research (2017) and AlBarashdi and Bouazza (2019). When not balanced properly, the very features and benefits also come with their own set of detriments.…”
Section: Discussionmentioning
confidence: 56%
See 3 more Smart Citations